Analysis on Factors Influencing the Participant’s Contribution of the Islamic Life Insurance in Indonesia - Vira Fidini Ristianty; Jaenal Efendi (UIN Siber Syekh Nurjati Cirebon, 2021)
Â AbstractThe development of the gross contribution and gross claims of Islamic life insurance has increased every year. In contrast to the growth in gross contribution and gross claims of Islamic life insurance, it has experienced fluctuating growth. The growth in gross claims should be balanced followed by the gross contribution, which shows an alignment between the growth in gross contributions and gross claims. This study aims to determine an overview of the growth and development of participantâ€™s contributions to the sharia life insurance industry in Indonesia and to analyze the effect of operational costs, claims, investment returns, risk-based minimum tabarru funds (DTMBR), company size, and tabarru funds. sharia law in Indonesia for the 2015-2019 period. This study uses panel data regression analysis with the help of Stata 14 software. The objects of this study are four full fledge companies and 16 sharia life insurance business units for the period 2015 to 2019. The results show that operational costs, claims, DTMBR, company size have a significant positive effect. to the contribution of sharia life insurance participants.